Occurrence, toxic effects and removal of metformin in the aquatic environments in the world: Recent trends and perspectives - Elizalde-Velázquez, Gustavo Axel; Gómez-Oliván, Leobardo Manuel (The Science of the total environment, 2020)
[Display omitted] •MET antidiabetic drug review was conducted.•The annual consumption of MET worldwide is in tons.•The occurrence of MET in the world ranges from ng L-1 to µg L-1.•MET toxic effects are embryotoxicity, teratogenicity and endocrine disruption.•Phytoremediation, adsorption and biodegradation are used to remove MET. Metformin (MET) is the most common drug used to treat type 2 diabetes, but also it is used as an anticancer agent and as a treatment for polycystic ovary syndrome. This drug is not metabolized in the human body, and may enter into the environment through different pathways. In wastewater treatments plants (WWTPs), this contaminant is mainly transformed to guanylurea (GUA). However, three further transformation products (TPs): (a) 2,4- diamino-1,3,5-triazine, 4-DAT; (b) 2-amino-4-methylamino-1,3,5-triazine, 2,4-AMT; and (c) methylbiguanide, MBG; have also been associated with its metabolism. MET, GUA and MBG have been found in WWTPs influents, effluents and surface waters. Furthermore, MET and GUA bioaccumulate in edible plants species, fish and mussels potentially contaminating the human food web. MET is also a potential endocrine disruptor in fish. Phytoremediation, adsorption and biodegradation have shown a high removal efficiency of MET, in laboratory. Nonetheless, these removal methods had less efficiency when tried in WWTPs. Therefore, MET and its TPs are a threat to the human being as well as to our environment. This review comprehensively discuss the (1) pathways of MET to the environment and its life-cycle, (2) occurrence of MET and its transformation products (3) removal, (4) toxic effects and (5) future trends and perspectives of possible methods of elimination in water in order to provide potential options for managing these contaminants.